Comparing the Rod-Like and Spherical BODIPY Nanoparticles in Cellular Imaging - Ma, Chong; Zhang, Jianxu; Zhang, Tao; Sun, Haojie; Wu, Jing; Shi, Jingwei; Xie, Zhigang (Frontiers in Chemistry, 2019)
To design efficient nanoparticles for bioimaging, it is necessary to systematically evaluate and develop nanoparticles with desired cellular uptake and intracellular fates. There are many studies have shown that cellular uptake largely depends on the geometric properties of nanoparticles. In this work, the organic nanoparticles with rod-like and spherical shapes were fabricated, and their cellular behaviours were studied and compared in detail via cellular uptake and bioimaging effect. The nanoparticles with spherical and rod-like morphology both can be internalized by HeLa and HepG2 cells, but the rod-like nanoparticles showed better imaging performance than their spherical counterpart. Above results presented that the rod-like nanoparticles possess great potential for bioimaging in efficient delivery and ideal imaging efficacy. Our studies may provide useful and fundamental information for designing efficient bioimaging systems.